História e literatura em ¨Eu o Supremo", de Antônio Augusto Roa Bastos - Savio, Eliane Dávilla (2017)
This dissertation intends to study the History of Paraguay and the literally works of Antônio Augusto Roa Bastos, by using as corpus his romance, I, the Supreme. This study has as a primary objective to demonstrate that, through interdisciplinarity it is possible to work History and Literature, broadening horizons and acquiring knowledge. It also intends to unravel a country that remains very much unknown, especially in educational institutions of the triple border, despite its many great authors, where Augusto Roa Bastos is just an example. To become familiar with his work and life is extremely important to the study of Hispanic-American Literature and, to understand it, it is necessary that said study is done in an interdisciplinary way, since his work it tied together with Paraguay’s History. Paraguay, a small country dominated by a dictatorial system for many years, which started with the Perpetual Dictator José Gaspar Rodriguez de Francia in 1811, when Paraguay’s independence from the Spanish Empire was decreed and ended with Alfredo Stroessner’s government in 1989. The data for this research was obtained through bibliographic fonts and readings of other thesis and dissertations (which are vast, showing that the author is objects of many studies in the academy). Because it is a theme that requires studying subjects related to History as social process and Literature as a form of expression for society – holder of historicity and a documental font for historic knowledge – this research show an analytical emphasis, with theoretical support from scholars from both areas.